1.
6sin^2x-3sinx*cosx-cos^2x=sin^2x+cos^2x
5sin^2x-3sinx*cosx-2cos^2x=0 /:cos^2x≠0
5tg^2x-3tgx-2=0
замена tgx=t
5t^2-3t-2=0
t=1
t=-2/5
обратная замена:
1) tgx=1
x=pi/4+pik, k∈Z
2) tgx=-2/5
x=-arctg(2/5)+pik, k∈Z
pi/4+pik, k∈Z
-arctg(2/5)+pik, k∈Z
2.
5sin^2x+3sinx*cosx-2cos^2x=3sin^2x+3cos^2x
2sin^2x+3sinx*cosx-5cos^2x=0 /:cos^2x≠0
2tg^2x+3tgx-5=0
замена tgx=t
2t^2+3t-5=0
t=1
t=-5/2
обратная замена:
1) tgx=1
x=pi/4+pik, k∈Z
2) tgx=-5/2
x=-arctg(5/2)+pik, k∈Z
pi/4+pik, k∈Z
-arctg(5/2)+pik, k∈Z
{3(х-у)-10=х+у,
{2(х-у)-13=х+у
{3х-3у-х-у=10,
{2х-2у-х-у=13
{2х-4у=10, /2
{х-3у=13
{х-2у=5,
{х-3у=13
Почленно отнимаем:
у=-8
Находим х:
х=2*(-8)+5=-11
ответ. -11 и -8